Trust Dynamics and Innovative Practices in Academic Environments - Adi Widodo; Muhamad Rizky Wijaya; Tias Pramono; Firdaus Putra; Dewiana Novitasari (Yayasan Aya Sophia Indonesia, 2024)
This study investigates the effects of interpersonal trust among private college lecturers in Tangerang (i.e., trust in colleagues and leaders) on innovative behavior and examines the mediating effect of knowledge sharing on this relationship. A total of 244 private college lecturers in Tangerang participated in this study. The results revealed that trust in coworkers and trust in leaders have positive effects on knowledge sharing activities. Although the effect of trust in colleagues on innovative behavior is not significant, trust in leaders has a significant effect on innovative behavior. The effect of lecturer knowledge sharing on innovative behavior was also found to be significant. In addition, the results show that knowledge sharing has a full mediating effect on the relationship between trust in colleagues and innovative behavior and a partial mediating effect on the relationship between trust in leaders and innovative behavior.